HUBUNGAN KUALITAS INTERAKSI ORANGTUA – ANAK DENGAN INTERAKSI TEMAN SEBAYA DI SMK MUHAMMADIYAH 2 PEKANBARU - Giovani Noversi; Raja Arlizon; Rosmawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract:The purpose of this research is to know the quality picture of the parent's interaction with the child, to know the description of the interaction of the child with peers and to know the relation of the quality of the parent-child interaction with peer interaction in vocational highschool Muhammadiyah 2 Pekanbaru. Technique of taking data in this research using questionnaire method, to collect data of parent interaction with child and child interaction with peer. Research subjects were all students of grade X vocational highschool Muhammadiyah 2 Pekanbaru which amounted to 370 students, but researchers only take 50% of students grade X. Determination of the sample by using random sampling technique. Data analysis was done by using percentage technique and Pearson product moment correlation. Where researchers choose grade X students due to the results of the phenomenon in the field. The results showed that the interaction of parents with children is in good category that is equal to 49.19% and interaction of children with peers are in good category that is equal to 81,08%. There is a positive relationship between parent-child interactions with peer interactions. This is evidenced by the correlation value of 0.709 and the value of p = 0.00.Key Words: Parent-Child Interaction, Child's Interaction With Peers.